A review of the genus Amphimonhystera Allgén, 1929 (Monhysterida: Xyalidae, Marine Freeliving Nematodes) with description of three new species - Tchesunov, Alexei V.; Mokievsky, Vadim O. (Zootaxa, 2005)
Four of the six known Amphimonhystera species are either redescribed or described including, A. galea Fadeeva, 1984, A. marisalbi sp. n., A. molloyensis sp. n. and A. pallida sp. n. (the two former species from the White Sea, Northern Russia and the two latter species from the Arctic deep sea). Generic diagnosis is emended and a pictorial key for identification of Amphimonhystera species is constructed. Characters of Amphimonhystera and some problems with Xyalidae taxonomy are discussed. Generotype A. anechma differs significantly from the other five Amphimonhystera species by having a tail tip devoid of terminal setae. A. marisalbi sp. n. is most similar to A. galea in general appearance and structural characters but differs from the latter by very low inner labial sensilla, lesser number of setae in the cephalic crown as well as by shorter setae of the cephalic crown and tail terminal setae. A. molloyensis sp. n. is distinctly separated from both A. galea and A. pallida sp. n. by very short setae of the cephalic circle and by proximal position of the amphids. A. pallida sp. n. differs from the more similar A. molloyensis sp. n. by a smaller and less elongate amphid and a longer distance from the anterior end to the amphid. The differences between A. pallida sp. n. and A. galea are shorter setae of the cephalic circle and a longer distance from the anterior end to the amphid.